Association between exposure to PM₁₀ and lung function performance among construction worker / Mohamad Hafifi Abdul Hamid - Abdul Hamid, Mohamad Hafifi (2015)
A crossectional study was carried out to the construction worker at Verdi Symphony Hills in Cyberjaya, Selangor comprised thirty (30) workers of construction worker and seventeen (17) workers from office worker as control group. The sample was selected randomly based on inclusive criteria which are nonsmoking and never experience any respiratory illness. Three procedures was conducted to the sample study which are Personal Air Monitoring to measure the exposure level of PMlO to the sample, Lung Function Test to measure the lung performance among sample and answering a series of questionnaire to identify symptom related with exposure to the PM₁₀ experience by samples. Findings shows there have significant different and correlation (p<0.05) between exposed ( construction worker) and unexposed group (office worker) in term of PM₁₀ exposure level and percentage of FEVl and FVC. Mean value for the exposure level to PM₁₀ gives 2.30±0.87 mg/nr' for the exposed group and 0.53±0.24 mg/m ' for the unexposed group. Percentage of FEVI gives means value about 64.73±16.793 and 87.06±5.202 and percentage of FVC gives 66.43±15.23 and 88.00±8.78 for the exposed and unexposed group respectively. The allergic symptom to the PMlO also shows significant association with group of respondent. As conclusion, it's clearly show relationship between exposure to the PMIO and Lung function Performance among the construction worker and responsible party must control the exposure by enforcement and supplying PPE to the worker.